MAJAPAHIT TROWULAN MUSEUM CATALOG AS HISTORICAL TOURISM EDUCATION AND CULTURAL HERITAGE PRESERVATION FOR ELEMENTARY SCHOOL - Puspitasari, Aditya Dyah; Putri, Anggita Bella Sah (Universitas Negeri Malang, 2024)
Limitations on the use of instructional media in the learning process in the classroom, students' lack of insight into history and teachers having difficulty teaching social studies content so that a media catalog was developed. This research is a development research using the ADDIE model which has five stages, namely analysis, design, develop, implementation, and evaluation. The purpose of this development research was to determine the validity, attractiveness, and effectiveness of the developed catalog learning media. The validity of the media catalog was obtained from design expert validators, material experts and media experts so that an average of 80% was obtained in the valid category. The attractiveness of the media catalog was obtained from a teacher and student response questionnaire in a large group trial with a percentage of 94.63% and 90.87% in the very interesting category. The effectiveness of the media catalog was obtained from observing teacher activity with a percentage of 91.66%, observing student activity 88.75%, student test results amounting to 83.3% with a very effective category. Based on the research results, the media catalog can be said to be valid, very interesting and very effective. Therefore, the media catalog is appropriate for use in theme 4, sub-theme 1, learning 3 and 4 in class V SDN Kebontemu